(untitled) (Jurnal Bahasa, 2011)
Rhythmic reduplication is one of word formation processes for Malay. However, there are problems in its classification and identification of its characteristics. This paper describes occurrences the rhythmic reduplication and defines their specific characteristics. By applying the Morpheme Doubling Theory (MDT) and the notion of "semantical copying" the ways in which words are rhythmically reduplicated are explained. Additionally, three formation models were also described. Based on these findings, four types of rhythmic reduplication are identified, includes two new formulas. Why rhythmic reduplication occurs can be explained although certain constraints do apply in certain aspects.